Diagnostic and therapeutic perspectives on low back pain in women with hypertension - Mayda, Laura; Kurniawati, Hidayatul; Yasmin, Sorfina; Fitriani, Rita (Science Midwifery, 2025)
Low back pain (LBP) affects approximately 9–12% of the global population at any given time. Most cases are nonspecific, occurring without a clear anatomical cause, and are typically managed with conservative approaches such as physiotherapy and light activity. This case involved a woman with LBP due to lumbar spondyloarthrosis and herniated nucleus pulposus (HNP) accompanied by hypertension. Her history of elevated blood pressure and frequent heavy lifting were recognized as significant risk factors, potentially affecting organ perfusion. The management provided in this case was appropriate and comprehensive, combining pharmacotherapy, physiotherapy as supportive therapy to enhance functional recovery, and comorbidity management. This integrated approach demonstrated effective clinical outcomes in addressing both the musculoskeletal and cardiovascular aspects of the patient’s condition.